Team Exploratory Testing Sessions. (5th April 2012) - Saukkoriipi, Soili; Tervonen, Ilkka
Abstract : Exploratory testing (ET) is popular, especially among agile development teams. In this paper, we study the team aspect in the ET context and explore how to use ET in team sessions to complement other testing activities. The goal was to define a team exploratory testing (TET) session approach and to provide evidence that the approach is worth using. A TET session approach is defined by means of parameters, roles, and process. Also, instructions for using the approach are given. The team is the key factor that gives the approach its value and distinguishes it from basic ET. The team enables greater access to expertise, experience, and information. The TET session approach enables participants with different professional background to join in the session. The sessions may be focused on different purposes; they can contribute to finding defects or learning the system, for example. With careful parameter definition, the approach's risks are mitigated.